Pengaruh Fasilitas Dan Tata Tertib Perpustakaan Terhadap Kepuasan Pemustaka Di Perpustakaan IAKN Tarutung - Simangunsong, Ulinarti (Jurnal Euangelion, 2024)
The aim of this research is to analyze 1) the influence of facilities on user satisfaction at the IAKN Tarutung Library; 2) the influence of rules and regulations on user satisfaction at the IAKN Tarutung Library; 3) the influence of facilities and rules together on user satisfaction at the IAKN Tarutung Library. The method used in this research is a quantitative research method. The population is all members of the IAKN Tarutung library in 2023/2024, namely 570 people and a sample of 86 people was determined using random sampling techniques. Data was collected using a closed questionnaire with 64 items. The results of data analysis show that: 1) the calculated F value > F table between library facilities and user satisfaction is 45.355 > 3.07, thus it is known that there is an influence of library facilities on user satisfaction at IAKN Tarutung, namely 35.1%, 2) value F count > F table between library rules and user satisfaction, namely 22.038 > 3.07, so it is known that there is an influence of library rules on user satisfaction at IAKN Tarutung, namely 20.8%, 3) F count > F table between facilities and library rules and regulations on user satisfaction, namely 25,831 > 3.07, thus it is known that there is an influence of library facilities and rules on user satisfaction at IAKN Tarutung, namely 38.4%, thus Ha is accepted and H0 is rejected.